PEMBERDAYAAN MASYARAKAT PETANI NELAYAN DI DESA TANGKASI KECAMATAN WORI KABUPATEN MINAHASA UTARA - Yakobus ., Bahabol; Benu Olfie L. Suzana; Melsje Yellie Memah (Sam Ratulangi University, 2021)
ABSTRACTThis study aims to find out what and how to empower the fishing farmer community in Tangkasi Village, Wori District, North Minahasa Regency. The research was conducted in Tangkasi Village, Wori District, North Minahasa Regency for 3 months from January to March 2021. The data used in this study were primary data and secondary data. Primary data is data obtained from the research field through a list of questions. Secondary data is data obtained from the village government, as well as scientific papers related to research. Sampling using purposive sampling method, the number of respondents as many as 15 people who are fishermen farmers. The analysis technique used in this research is descriptive. Based on the results of the research, it is known that fishing farmers are involved in community empowerment activities by the Village Government, either through the application of seaweed cultivation, training in making meatballs, and additional efforts to tailor clothes and boat manufacture, and they continue to develop according to the skills they have. in various sectors so that the economy rebounds.